2005
DOI: 10.1002/masy.200550113
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐Alginate Nanoparticles Formed by Reverse Microemulsion as Gene Carriers

Abstract: Natural biopolymers are widely used in the field of drug and gene delivery. In this study, alginate nanoparticles were prepared using water‐in‐oil microemulsion as a template followed by calcium crosslinking of guluronic acid units of alginate polymer. After collected by ultracentrifugation, alginate nanoparticles were analyzed by electron microscopy to obtain the size and morphology which were varied with the ratio of water, oil, and surfactant used. To examine the potency of Ca‐alginate nanoparticles as carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…[19][20][21] Alginate nanoparticles owing to biocompatibility, biodegradability, nonantigenicity, gelation ability, and mucoadhesive advantages have been extensively applied as drug/gene delivery systems. [22][23][24] The most common techniques used for the preparation of alginate nanoparticles are the reverse microemulsion, 25 desolvation, 26 cross-linking, 27 and evaporation.…”
Section: Alginatementioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Alginate nanoparticles owing to biocompatibility, biodegradability, nonantigenicity, gelation ability, and mucoadhesive advantages have been extensively applied as drug/gene delivery systems. [22][23][24] The most common techniques used for the preparation of alginate nanoparticles are the reverse microemulsion, 25 desolvation, 26 cross-linking, 27 and evaporation.…”
Section: Alginatementioning
confidence: 99%
“…30 After the endocytosis of alginate nanoparticles, rapid erosion and osmotic swelling results in the endosomal escape and intracellular localization of gene. 87 For example, coating of chitosan nanoparticles with alginate increased the gene escape before arriving digestive endolysosomal vesicles and enhanced the transfection rate in NIH 3T3 cells. 88 Jin-Oh You et al reported the transfection of plasmid-loaded calcium-alginate nanoparticles by NIH 3T3 cells.…”
Section: Polysaccharide Nanoparticles For Gene Deliverymentioning
confidence: 99%
“…For example, 250-850 nm (depending on the alginate concentration) particles were synthesized as drug carriers; these particles are formed in solution by adding sodium alginate, calcium chloride and then poly-L-lysine [43]. The particle size can also be controlled by the volume of "nanoreactors" (micelles); reverse micelles were successfully used to synthesize nanocarriers (from alginate and calcium salts) with an average size of about 80 nm in diameter exhibiting a high degree of endocytosis by NIH 3T3 cells [44]. It is also possible to combine the surfactant and the cationic polymer to tune the size of alginate particles.…”
Section: The Hypothesis Assessment and Reviewmentioning
confidence: 99%
“…For example, Ca-alginate nanoparticles have been prepared by water-in-oil reverse microemulsion method (~80 nm in size) [169] and ion-induced gelification method (235.5nmin size) [170] to deliver gene and drugs, respectively. The relative bioavailabilities of all drugs encapsulated were significantly higher than oral free drugs.…”
Section: Ionic Crosslinking Polysaccharide Nanoparticlesmentioning
confidence: 99%